2020
DOI: 10.1055/s-0040-1708898
|View full text |Cite
|
Sign up to set email alerts
|

Time between Diagnosis and Treatment of Hypopharynx and Larynx Cancer: Are Longer Delays Associated with Higher Discrepancy between Clinical and Pathological Staging?

Abstract: Introduction At the time of diagnosis, treatment strategies for cancer are largely based upon clinical staging. However, discrepancy between clinical and pathological staging has been reported. Objective To assess the rate of staging discrepancy in Laryngeal and Hypopharyngeal Squamous Cell Carcinoma (LHSCC), the potential influence of higher interval of time from diagnosis to primary surgical treatment, and whether this has any impact on survival outcomes. Methods Retrospective study of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The age at presentation and male predominance in the present study were similar to what has been previously presented. 8 9 11 13 15 On the other hand, tobacco and alcohol consumption were not as frequent as previously reported, 8 9 11 probably due to lack of information on clinical data. The clinical staging in this population was I/II in 39.3% and III/IV in 60.7%, which is more balanced when compared with previous studies with a higher inclusion of advanced disease 8 9 11 or with another study with a higher rate of initial stages of the disease.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The age at presentation and male predominance in the present study were similar to what has been previously presented. 8 9 11 13 15 On the other hand, tobacco and alcohol consumption were not as frequent as previously reported, 8 9 11 probably due to lack of information on clinical data. The clinical staging in this population was I/II in 39.3% and III/IV in 60.7%, which is more balanced when compared with previous studies with a higher inclusion of advanced disease 8 9 11 or with another study with a higher rate of initial stages of the disease.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, the survival analysis may have been biased by the significant number of censored patients, even though there was a similar censored rate among all groups. Previous reports have also showed no differences in mortality or disease-free survival among groups, 9,11,14,15 which may be explained by treatment adjustments according to pathological staging, in which upstaging a patient may enable appropriate adjuvant treatment and downstaging a patient may prevent unnecessary morbidity from excessive adjuvant treatment. On the other hand, other retrospective studies have shown increased mortality on pathological T upstaging, 13 nodal upstaging, 8 or both.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…All these findings contribute to assessing the clinical TMN (cTMN) classification. In addition, a detailed histopathological analysis performed on the tumor specimens defines the pathological TMN (pTMN) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%